The Association of Vitamin D Deficiency with Dental Health - Hasaballah, Nabaa (Journal of Neonatal Surgery, 2025)
This research discusses the association between Vitamin D deficiency and dental health. It highlights that low Vitamin D levels can lead to cavities, gum disease, and tooth loss. The study utilized surveys, dental exams, and blood tests to gather data. The 100 participants were recruited from local clinics and health centers. The findings indicate that older adults often exhibit poor dental health and low Vitamin D levels. The study explains Vitamin D's role in calcium absorption and immune support. It also reveals that awareness of Vitamin D's benefits is low, which prolongs the timeframe before individuals seek sun exposure, a balanced diet, and supplements. Limitations of the study include a small sample size and reliance on self-reported data. The study emphasizes the need for better education on Vitamin D and suggests lifestyle changes to prevent dental disease. It concludes by recommending further studies on this topic.